PENGARUH KUALITAS PRODUK, HARGA DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA VARIO 125 FI ( Studi Kasus Pada Pengguna Honda Vario 125 FI Di Kec. Juwana ) - Fevri Setya Nugroho; Handoyo Djoko Waluyo; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2015)
This study aimed to determine the effect of product quality, price, and promotion of the product purchase decisions. Researchers conducted a study on the sale of Motorcycle Honda Vario 125 FI in Juwana Subdistrict.This research was conducted with survey methods (interviews and questionnaires) to 50 ( Fifty) of the respondents, the sampling selection technique using purposive sampling. The data obtained were analyzed quantitatively by using tools such as cross-table analysis, validity, reliability, simple linear regression, multiple linear regression, coefficient of determination and testing with T test  and test  F. The independent variable is the quality of the product, price and promotion, while the dependent variable is the purchase decision.The results showed no effect of product quality on purchasing decisions by 46.7%. The effect of price to quality is 61.7% of purchase decisions and influence on purchasing decisions promotion 59.9%. Taken together the quality of the product, price and promotion has the effect of 72.4%, which means that consumer perceptions of product, price and promisi proportional or positive, which if consumers assess the quality of the product, price, promotion of good will increase the sales of this product.Suggestions for the company is to continue to maintain the quality of products by regularly monitoring the quality of the basic ingredients of products, giving a discount on the purchase of products and continues to promote the increase of the personal selling product knowledge in order to provide solutions